Ritalin in children with attention deficit hyperactivity disorder (Research, Society and Development, 2022)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is characterized by symptoms of: inattention, hyperactivity and impulsivity. The treatment must be multimodal, combining the use of psychotropic drugs with psychosocial interventions and Cognitive-Behavioral Therapy (CBT) is one of the psychotherapies indicated to treat this pathology. Objective: The main objective for the realization of this article is given by the need to know better about Attention Deficit Hyperactivity Disorder, as well as its causes and consequences and also to know better about the medication used as one of the forms of treatment being in this case Ritalin. Methodology: the research was developed through searches on the Scielo (Electronic Library Scientifc Electronic Library Online) and Lilacs platforms. Based on a literature review, according to Silva (2019) , using terms and descriptors related to the use of Ritalin in children with attention deficit hyperactivity disorder. Articles that did not meet the inclusion criteria, those that presented data duplication and articles that, after a detailed reading, did not meet the objective proposed in this review were excluded. Finally, 24 publications were selected to compose the study. Conclusion: The problem of ADHD goes beyond the reported symptoms, but their presence leads to negative consequences, interfering with the psyche, memory, family and social relationships and, later, in the professional life of the person affected.